An investigation on the position errors of resolvers designed in different structures: A review - Celikel, Resat; Boztas, Gullu; Aydogmus, Omur (Elsevier Sci Ltd, 2023)
Absolute position information of electric motors or rotating mechanical parts used in some industrial applications is critical. This information can be measured either digitally using an absolute encoder or analog using a resolver. Resolvers are preferred in many areas of the industry due to their many advantages and different physical structures. In addition, resolvers are preferred according to the application in which they are used, considering their different physical structures and measurement errors. In this study, a general review of the subject has been made by examining studies on resolvers until today. Resolvers are classified into four main types according to their structures: wound rotor, reluctance rotor, permanent magnet auxiliary excitation and printed circuit-based. The paper presents a review of the measurement errors and technical characteristics of different resolver types.
Keywords: Absolute position; Electrical motors; Resolver; Robotics